Tardigrade: Leveraging Lightweight Virtual Machines to Easily and Efficiently Construct Fault-Tolerant Services - Lorch, Jay; Baumann, Andrew; Glendenning, Lisa; Meyer, Dutch T.; Warfield, Andrew (12th USENIX Symposium on Networked Systems Design and Implementation (NSDI'15), 2015)
Many services need to survive machine failures, but designing and deploying fault-tolerant services can be difficult and error-prone. In this work, we present Tardigrade, a system that deploys an existing, unmodified binary as a fault-tolerant service. Tardigrade replicates the service on several machines so that it continues running even when some of them fail. Yet, it keeps the service states synchronized so clients see strongly consistent results. To achieve this efficiently, we use lightweight virtual machine replication. A lightweight virtual machine is a process sandboxed so that its external dependencies are completely encapsulated, enabling it to be migrated across machines. To let unmodified binaries run within such a sandbox, the sandbox also contains a library OS providing the expected API. We evaluate Tardigrade's performance and demonstrate its applicability to a variety of services, showing that it can convert these services into fault-tolerant ones transparently and efficiently.